An imidazole functionalized pentameric thiophene displays different staining patterns in normal and malignant cells - Magnusson, Karin; Appelqvist, Hanna; Cieślar-Pobuda, Artur; Bäck, Marcus; Kågedal, Bertil; Jonasson, Jon A.; Los, Marek J.; Nilsson, K. Peter R. (Frontiers in Chemistry, 2015)
Molecular tools for fluorescent imaging of cells and their components are vital for understanding the function and activity of cells. Here, we report an imidazole functionalized pentameric oligothiophene, p-HTIm, that can be utilized for fluorescent imaging of cells. p-HTIm fluorescence in normal cells appeared in a peripheral punctate pattern partially co-localized with lysosomes, whereas a one-sided perinuclear Golgi associated localization of the dye was observed in malignant cells. The uptake of p-HTIm was temperature dependent and the intracellular target was reached within 1 h after staining. The ability of p-HTIm to stain cells was reduced when the imidazole side chain was chemically altered, verifying that specific imidazole side-chain functionalities are necessary for achieving the observed cellular staining. Our findings confirm that properly functionalized oligothiophenes can be utilized as fluorescent tools for vital staining of cells and that the selectivity towards distinct intracellular targets are highly dependent on the side-chain functionalities along the conjugated thiophene backbone.